The 21st Century Transformation of Islamic Religious Education (PAI) Learning Through Active Deep Learner Experience (ADLX): Teachers’ Strategies, Students’ Responses, And Challenges in Elementary School - Purwaningrum, Septiana; Maknun, Lu’luil (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Islamic Religious Education (PAI) learning in elementary schools is often still traditional, teacher-centered, and focused on memorization, which makes it less meaningful for students. Ideally, PAI learning should foster active, reflective, and applicable processes in daily life. This study aims to describe the implementation of the Active Deep Learner Experience (ADLX) method in PAI learning at SDIT Bina Insani, Kediri City, focusing on teachers’ strategies, students’ responses, and challenges faced during its implementation. This research employed a qualitative descriptive approach, with data collected through participatory observation, in-depth interviews, and documentation. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that teachers applied structured strategies aligned with ADLX principles, involving students actively and reflectively in the learning process. Students responded positively, as shown by increased participation, deeper conceptual understanding, value internalization, and improved worship practices. However, teachers faced challenges such as limited instructional time, diverse student characteristics, and restricted learning media. The study concludes that ADLX is effective in improving the quality of PAI learning across cognitive, affective, and psychomotor domains. These findings imply the need for institutional support in terms of resource provision, flexible policies, and continuous teacher training to ensure the sustainable implementation of ADLX.